Microstructure and corrosion resistance of stainless steel manufactured by laser melting deposition. (May 2021) - Yang, S.F.; Li, C.W.; Chen, A.Y.; Gan, B.; Gu, J.F.
Graphical abstract: Highlights: Stainless steel plates were produced by laser melting deposition (LMD). Cellular structures with enrichments of alloy elements at interface are observed. LMDed specimens exhibit high corrosion resistance in salt solution. The enrichments of Cr and Mo elements at the interfaces enhance the passivation. Abstract: Additive manufacturing can not only fabricate complicate shaped parts, but also produce new non-equilibrium structures during the rapid heating and cooling process, involving new solid-solution phases and inhomogeous elemental distribution. The 316 L stainless steel (SS) plates were manufactured by laser melting deposition, and the effects of non-equilibrium structures on the corrosion resistance are investigated. The microstructures of the manufactured specimens are analyzed by X-ray diffraction, scanning electron microscopy, electron backscatter diffraction, and transmission electron microscopy. The corrosion performances are evaluated by electrochemical tests and salt spray tests in NaCl solution. The microstructures of the manufactured 316 L SS specimen are composed of cellular structures, where the boundaries of the cellular structures are enriched with Cr, Mn, Mo, and Nb elements. These cellular structures can significantly enhance the corrosion resistance, representing by higher open circuit potential and small pitting pores compared with the commercial 316 L SS. The reasons of the improved corrosion resistance can be attributed to the high densification and fine cellular structures with the enrichment of Cr and Mo elements at the interfaces.